Insight into mycelium-lignocellulosic bio-composites: Essential factors and properties. (October 2022) - Sun, Wenjing; Tajvidi, Mehdi; Howell, Caitlin; Hunt, Christopher G.
Graphical abstract: Highlights: Fungal mycelia behave differently in low-density vs. high-density composites. For as-grown foams, thickness recovery and stiffness increase with hyphal growth. Mycelia reinforce hot-pressed panels by growing across gaps and adhering particles. Abstract: Mycelium-bonded bio-composites are promising new materials for replacing non-sustainable products. In such composite systems, fungal mycelia work as an adhesive, bonding together lignocellulosic substrate particles. In this work, we focus on the two groups of mycelium-bonded bio-composites: as-grown foams and hot-pressed (densified) panels. We used Trametes versicolor mycelium and yellow birch wood particles as a substrate and incubated the mixture for up to 30 days. We investigated the relationship between mycelium growth and essential end-use properties. We revealed that in as-grown foams, mycelial colonization does not significantly alter physical and mechanical properties but can reduce sound absorption. In contrast, increased mycelial density in hot-pressed panel products resulted in an increasing modulus of rupture, modulus of elasticity, and internal bond strength. In hot pressed panels, mycelia appear to act as an adhesive to bond particles forced into contact during compaction.